(untitled) (Intent Research Scientific Journal, 2025)
The study aimed mainly to identify the social, economic and cultural factors leading to addiction to narcotic drugs among Iraqi youth from the point of view of students at Iraqi universities, to achieve the objectives of the study, the study was based on the descriptive analytical method using the sample social survey method, to obtain field data from the study sample using the questionnaire tool, and the study sample consisted of (650) students.